CHARCOAL QUALITY FOR DOMESTIC USE - Garcia, D. P.; Rodrigues, C.R.; Dal Bem, E. A.; Ferreira, J. P. (Revista Brasileira de Engenharia de Biossistemas, 2017)
Brazil is the world's largest producer and consumer of charcoal. Only the steel industries consume about 70% of the national production. Residential and commercial applications use 0.14% of this production, representing a consumption of 871,000 t in 2015. Although there are many articles on charcoal, there are few that deal with quality, especially in comparison with the standards established in Resolution 40, of the Secretariat of Supply and Agriculture. In this way, this article makes an evaluation of charcoal, comparing them with this quality standard. Based on five commercial samples, moisture, ash, volatile materials, fixed carbon, higher calorific value and packaging labels were adopted as characteristic variables of quality. Thus, among the 25 parameters evaluated, 36% were not attended. Concluding that the samples presented low quality for domestic use and companies do not meet minimum quality requirements for the product.